2014
DOI: 10.1590/2317-1545v36n41032
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and sanitary quality, and transmission of fungi associated with Brachiaria brizantha (Hochst. ex. A. Rich.) Stapf seeds submitted to thermal and chemical treatments

Abstract: -The Brazilian pastures establishment success depends on the use of seeds with high physiological and sanitary quality. The aim of this study was to evaluate the effect of thermal and chemical treatments on quality of Brachiaria brizantha, cv. BRS Piatã and pathogen transmission via seed. The treatments included the use of fungicides, detergent, sodium hypochlorite, sulfuric acid and alcohol, as well as thermal treatments. In addition to seeds without treatment, nine treatments were tested.The tests used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…From the seeds sanitary analysis, it was verified that the results of fungi incidence obtained by the authors cited in the reference [17,18,19,20] corroborate with those found in the present study (Alternaria sp., Aspergillus sp., Bipolaris sp., Cladosporium sp., Cercospora sp., Fusarium sp., Nigrospora sp., Penicillium sp., Rhizoctonia sp. e Rhizopus sp.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…From the seeds sanitary analysis, it was verified that the results of fungi incidence obtained by the authors cited in the reference [17,18,19,20] corroborate with those found in the present study (Alternaria sp., Aspergillus sp., Bipolaris sp., Cladosporium sp., Cercospora sp., Fusarium sp., Nigrospora sp., Penicillium sp., Rhizoctonia sp. e Rhizopus sp.…”
Section: Discussionsupporting
confidence: 91%
“…In studies performed by the authors cited in the reference [19,20], they verified the presence of the fungi Aspergillus niger, Bipolaris sp., Fusarium sp., Penicillium sp. and Rhizopus sp.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the other seed batches, no occurrence of this fungus was detected. This genus has been reported in the leaves of B. brizantha 'BRS Piatã' and Brachiaria decumbens (Sbalcheiro et al, 2014). In B. decumbens, the occurrence of Pithomyces sp.…”
Section: Resultsmentioning
confidence: 94%